Modelling of the human knee joint supported by active orthosis - Musalimov, V.; Monahov, Y.; Tamre, Mart; Röbak, Dmitri; Sivitski, Alina; Aryassov, Gennady; Penkov, Igor (Zielona Góra: Uniwersytet Zielonogórski)
The article discusses motion of a healthy knee joint in the sagittal plane and motion of an injured knee joint supported by an active orthosis. A kinematic scheme of a mechanism for the simulation of a knee joint motion is developed and motion of healthy and injured knee joints are modelled in Matlab. Angles between links, which simulate the femur and tibia are controlled by Simulink block of Model predictive control (MPC).
Keywords: knee joint; modelling; active orthoses; biomechatronics